HUBUNGAN PEMAHAMAN LINGKUNGAN ALAM DENGAN SIKAP PEDULI LINGKUNGAN MUATAN IPA SISWA KELAS V SDN DI KELURAHAN CENGKARENG TIMUR JAKARTA BARAT - Angelika, Tio Fanny; Endang Wahyudiana; Taofik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between naturalist intelligence and environmental awareness of science content of grade V students of SDN in Cengkareng Timur Village, West Jakarta. The method used is quantitative correlation with data collection techniques in the form of multiple-choice tests to measure naturalist intelligence and Likert scale questionnaires to measure environmental awareness. The sample consisted of 91 students taken using simple random sampling techniques from two schools. The results of data analysis showed that there was a significant positive relationship between naturalist intelligence and environmental awareness with a Pearson correlation coefficient value of 0.795 and a significance of 0.001 (<0.05). The determination test showed that 63.2% of environmental awareness was influenced by naturalist intelligence, the remaining 36.8% was influenced by other factors. This finding strengthens the theory of multiple intelligences regarding naturalist intelligence put forward by Howard Gardner, in addition the theory was strengthened by Armstrong in increasing naturalist intelligence in schools contributing to the formation of students' environmental awareness.